Research on dynamic characteristics of shoegear-conductor rail system considering conductor rail joint gap - YU Wenbin (机车电传动)
In urban rail transit, in addition to overhead catenary system, the electric shoegear-conductor rail system is often used for energy supply of trains. In the shoegear-conductor rail system, the electric shoegear slides along the conductor rail, and the vibration behavior is complex and vulnerable to the influence of line conditions and the structure itself. When the conductor rail has rail joint gap, the shoegear passing through will generate large impact force, resulting in the deterioration of the current collection quality of the shoegear-conductor rail system. Based on multi-body dynamics and finite element theory, this paper built a shoegear-conductor rail coupling dynamics model, and compared it with measured data to verify the accuracy of the model. Based on the model, the dynamic performance of the shoegear-conductor rail system at different speeds and with rail joint gaps in different directions was analyzed, considering the worst conductor rail joint gap conditions specified in the standard. The results show that when the shoegear passes through the front-high-rear-low rail joint gaps, the vehicle running speed has a more serious influence on the current collection quality of the shoegear-conductor rail system compared to the front-low-rear-high rail joint gaps.